EXPLORING THE USE OF SPOTIFY ON ENHANCING EFL STUDENTS’ VOCABULARY - Putri Hidayah, Amelia; Wintolo Apoko, Tri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Vocabulary acquisition is essential for EFL students to develop their language skills. However, traditional vocabulary learning methods often fail to engage students effectively. This study investigates the use of Spotify as a tool to enhance EFL students’ vocabulary mastery in a vocational high school context. A mixed-method approach was used, combining questionnaires and semi-structured interviews with two classes of students from hospitality department. The study explores how students use Spotify, particularly song lyrics, to learn vocabulary, their perceptions of its effectiveness, and the challenges they face. Findings show that students find Spotify engaging and helpful in learning new words, especially through repeated listening and contextual understanding. However, challenges include slang use and difficulty in understanding some lyrics. The study concludes that Spotify can serve as a valuable supplementary tool for vocabulary learning and offers practical insights for integrating music-based learning in EFL classrooms.